Regional Typology Analysis and Potential Business Fields in Maluku Province - Bugis, Muhammad; Wahyuningsih, Tri; Abbas, Djamila (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
Decentralization necessitates the provincial government to maximize its potential to increase regional revenues. This study aims to categorize regencies and cities in a developing province, i.e., Maluku, based on economic growth and the Human Development Index (HDI) and thus identify potential and non-potential business fields. This study collected secondary data in economic growth data, Human Development Index (HDI), and Gross Regional Domestic Product (GRDP) From 2013 to 2017 and is analyzed by the Klassen Tipology method. The results show that Ambon City is classified as a developed region with potential business fields in Maluku Province, including agriculture, forestry and fishery, construction, and wholesale and retail trade. The results provide a detailed description of the potential development of the business sector and will serve as a guideline for stakeholders.